Keanekaragaman dan Karakteristik Morfometrik Ikan Air Tawar di Sungai Lais Kecamatan Lais Kabupaten Bengkulu Utara Provinsi Bengkulu - Pariyanto Pariyanto; Apriza Fitriani; Panji Prasatyo (bionature, 2021)
Abstract. This study aims to determine the diversity and characteristics of freshwater fish in Sungai lais, lais sub-district, Bengkulu Utara district, Bengkulu province. This research was conducted using survey methods and to obtain primary data taken into the field by direct capture. Samples were taken in sungai lais, lais sub-district, Bengkulu Utara regency is done by dividing 3 stations. Measurement of fish morphometric characteristics is done by measuring fish body parts including, total length (PT), standard length (PB), head length (PK), height (TB), body width (LB) and tail height (TE). The results showed that the diversity index which is found in the lais river which is classified as low, with a diversity index at station A 0.666, station B 0.724 and station C 0.522. The types of fish found in this study consisted of 8 species namely Cyprinus carpio (goldfish), Osteohilus vittatus (palau fish), Anabas testudienus (fish betok), Channa striata (cork fish), Oreochromis niloticus (tilapia), Oreochromis mossambicus (tilapia fish), Trighogaster trichopterus (sepat fish), and Clarias batrachus (catfish).Keywords: Diversity, Fish, Lais River, Morphometric Characteristic